SSL/TLS protocol on post-quantum algorithms - Milevskyi, Stanislav; Voropay, Natalya; Korol, Olha; Yevseiev, Serhii; Aksonova, Iryna (Національний авіаційний університет, 2024)
The development of mobile technologies and their integration with Internet of Things and smart technologies form both cyber-physical and socio-cyber-physical systems. In such systems, as a rule, wireless communication channels are used, in which SSL/TLS protocols are used to provide security services (confidentiality, integrity and authenticity). However, this protocol is not only vulnerable to "Meeting in the Middle", POODLE, BEAST, CRIME, BREACH attacks, but with the advent of a full-scale quantum computer, it can be broken. The article proposes a protocol based on quantum algorithms – crypto-code constructions, which will ensure not only resistance to current attacks, but also stability in the post-quantum period. To ensure the "hybridity" of services, it is proposed to use McEliece and Niederreiter crypto-code constructions and the improved UMAC algorithm based on McEliece crypto-code design. The use of crypto-code constructions provides not only resistance to attacks, but also simplifies the formation of a connection – the parameters of elliptic curves are used for the transmission of the common key. This approach significantly reduces the time of connecting mobile gadgets and simplifies the procedure of agreement before data transfer.

Розвиток мобільних технологій та їх інтеграція з Інтернетом речей і розумними технологіями формують як кіберфізичні, так і соціально-кіберфізичні системи. У таких системах, як правило, використо-вуються бездротові канали зв'язку, в яких для надання послуг безпеки (конфіденційності, цілісності та автентичності) використовуються протоколи SSL/TLS. Однак цей протокол не тільки вразливий до атак "Meeting in the Middle", POODLE, BEAST, CRIME, BREACH, але з появою повномасштабного квантового комп’ютера його можна зламати. У статті запропоновано протокол на основі квантових алгоритмів – криптокодових конструкцій, який забезпечить не лише стійкість до поточних атак, а й стабільність у пост-квантовий період. Для забезпечення «гібридності» сервісів пропонується використовувати конструкції криптокодів МакЕліса і Нідеррайтера і вдосконалений алгоритм UMAC на основі дизайну криптокодів МакЕліса. Використання криптокодових конструкцій забезпечує не тільки стійкість до атак, але й спрощує формування з’єднання – для передачі загального ключа використовуються параметри еліптичних кривих. Такий підхід значно скорочує час підключення мобільних гаджетів і спрощує процедуру узгодження перед передачею даних.
Протокол SSL/TLS на постквантових алгоритмах
Keywords: SSL/TLS protocol; crypto-code constructions; UMAC algorithm; algebraic geometric codes; lossy codes; протокол SSL/TLS; криптокодові конструкції; алгоритм UMAC; алгебраїчні геометричні коди; коди з втратами